NEW PERIOD OF THE LONGITUDINAL MAGNETIC FIELD VARIABILITY IN Ap STAR γ EQU - Bychkov, V. D.; Bychkova, L. V.; Madej, J. (Одеські астрономічні публікації, 2017)
We present an analysis of the secular variability of the longitudinal magnetic field Be in the roAp star γ Equ (HD 201601). Measurements of the stellar magnetic field Be were mostly compiled from the literature. We appended our new 33 Be observations which were obtained at the Special Astrophysical Observatory. All the available data cover the time period of 58 years, and include both phases of the maximum and minimum Be. We determined that the period of long-term magnetic variations in γ Equ equals to 91.1 ± 3.6 years.